Metabolites mediate the effects of healthy lifestyles on the risks of common age-related diseases - Li, Yan; Li, Huijuan; Chen, Xiaoyu; Liang, Xueyan (Frontiers in Endocrinology, 2025)
BackgroundLimited research is available on the associations between healthy lifestyles and age-related diseases, particularly those involving multiple diseases and their underlying mechanisms. We aimed to determine whether healthy lifestyles are associated with a lower likelihood of age-related diseases, and whether metabolites mediate these associations.MethodsThe UK Biobank data cohort was used in this study. Five lifestyle factors (diet, physical activity, sedentary behavior, sleep duration, and alcohol consumption) were combined to determine that composite lifestyle scores. Lifestyle-related metabolic signatures were analyzed using Cox proportional hazards models. We then conducted sequential analyses combining Cox regression, linear regression, extreme gradient boosting (XGBoost), and Shapley additive explanation (SHAP) values to identify metabolites associated with age-related diseases and healthy lifestyle scores. Mediation analysis was performed to investigate the potential mediating effects of the identified metabolites on age-related diseases.ResultsHealthy lifestyle scores contributed the most to prevention of chronic obstructive pulmonary disease (COPD) (hazard ratio [HR] [95% confidence interval (CI): 0.72 (0.71, 0.74)], followed by emphysema [HR (95% CI): 0.75 (0.71, 0.78)]. Furthermore, intermediate or healthy lifestyles significantly decreased the age-related risk of stroke, chronic liver disease, chronic kidney disease (CKD), osteoporosis, osteoarthritis, and hypertension. Age-related diseases were associated with the top 10 metabolites, and these associations were individually or jointly mediated. For example, glycoprotein acetylation contributed 14.43% to the overall association between healthy lifestyle scores and inflammatory bowel disease (IBD), whereas low-density lipoprotein (LDL) cholesterol level attenuated this association by 2.92%, the fatty acid content based on the degree of unsaturation showed a 21.64% contribution to the association between the healthy lifestyle score and type 2 diabetes, whereas cholesterol esters in large high-density lipoproteins (HDLs) accounted for 4.57%. Sensitivity analyses verified the robustness and validity of these findings.ConclusionsThese findings provide a deeper understanding of the intricate relationships among lifestyle and metabolites and the development of age-related diseases.